Dinâmica de formação de biofilmes por Salmonella Enteritidis sob diferentes temperaturas e o efeito de tratamentos para a remoção - Webber, Bruna (2015)
Salmonella Enteritidis has emerged as the most common serotype in humans worldwide and is the main cause of outbreaks of foodborne diseases. Salmonella spp. can adhere and form biofilms on inert food processing surfaces which, once formed, act as points of constant contamination. Micro-organisms in the sessile form are significantly more resistant to the agents used in the hygienic procedures, which consist in the use of hot water, detergents and sanitizers, in order to reduce the microorganisms to safe levels and obtain a product of good hygienic-sanitary quality. Based on the relevance of these themes, this dissertation was elaborated with two scientific papers. In Chapter 1 we compared two laboratory methods to remove Salmonella spp. Biofilms, grown in vitro on a stainless steel surface from the food industry. Vortex vortexing for 2 min and sonication for 10 min (ultrasonic bath, 40 kHz frequency and 81 W power) were used in the stripping step. Although we did not find a statistical difference between the methods, the use of ultrasound was chosen as the standard for the deafness due to its ease of use and the hydrodynamic properties that destabilize the structure of the biofilm. Chapter 2 evaluated the ability of SE to form biofilm on different surfaces and hygiene processes. In the hygienization procedures the coupons remained for 3 minutes immersed in sterile water heated at 45 ° C and at 85 ° C, and in solutions of 0.5% peracetic acid and 1% quaternary ammonia for 5 minutes. Bacterial adhesion indicated that both SEs adhered to polyethylene, polyurethane and stainless steel. Among the exposure temperatures, SE 84 and SE 106 adhered under all exposure temperatures, 3 ° C, 9 ° C, 25 ° C, 36 ° C and 42 ° C, increasing adhesion as temperature rose, but without statistical difference. Peracetic acid and water at 85 ° C had similar action on biofilm removal. The water at 45ºC was not effective, being close to the control. The other tested sanitizer, quaternary ammonia, removed biofilm, but less efficiently compared to peracetic acid. In general, the results demonstrated that these materials, used in the food industry, provided the adhesion of SE to the different environmental conditions. Emphasis is given to the formation of biofilms at refrigeration temperatures, mainly at 3 ° C, hitherto not described as possible for growth of Salmonella spp. on these surfaces. Our results are therefore important for the development of control strategies for Salmonella biofilms and may help the poultry industry to have a better knowledge of the actual conditions of the slaughterhouses, leading to an improvement in the hygienic conditions of these establishments